MMS21/HPY2 and SIZ1, two Arabidopsis SUMO E3 ligases, have distinct functions in development. - Takashi Ishida (Public Library of Science (PLoS), 2012)
The small ubiquitin related modifier (SUMO)-mediated posttranslational protein modification is widely conserved among eukaryotes. Similar to ubiquitination, SUMO modifications are attached to the substrate protein through three reaction steps by the E1, E2 and E3 enzymes. To date, multiple families of SUMO E3 ligases have been reported in yeast and animals, but only two types of E3 ligases have been identified in Arabidopsis: SAP and Miz 1 (SIZ1) and Methyl Methanesulfonate-Sensitivity protein 21 (MMS21)/HIGH PLOIDY 2 (HPY2), hereafter referred to as HPY2. Both proteins possess characteristic motifs termed Siz/PIAS RING (SP-RING) domains, and these motifs are conserved throughout the plant kingdom. Previous studies have shown that loss-of-function mutations in HPY2 or SIZ1 cause dwarf phenotypes and that the phenotype of siz1-2 is caused by the accumulation of salicylic acid (SA). However, we demonstrate here that the phenotype of hpy2-1 does not depend on SA accumulation. Consistently, the expression of SIZ1 driven by the HPY2 promoter does not complement the hpy2-1 phenotypes, indicating that they are not functional homologs. Lastly, we show that the siz1-2 and hpy2-1 double mutant results in embryonic lethality, supporting the hypothesis that they have non-overlapping roles during embryogenesis. Together, these results suggest that SIZ1 and HPY2 function independently and that their combined SUMOylation is essential for plant development.